Subchronic toxicity studies of cocoa pod husk pectin intended as a pharmaceutical excipient in Sprague Dawley rats - Ofosua Adi-Dako; Kwabena Ofori-Kwakye; Kennedy K.E. Kukuia; Jerry Asiedu-Larbi; Alexander Nyarko; Doris Kumadoh; Christina Osei-Asare (GarVal Editorial Ltda., 2018)
Context: Excipients play a key role in the quality of medicines and contribute to viable delivery systems. This has intensified the search for new natural polymer pharmaceutical excipients. Cocoa pod husks (CPHs) are a rich source of pectin. A study of CPH pectin showed that it possesses the requisite physicochemical properties to be employed as a multi-functional pharmaceutical excipient. However, the safety of this natural polymer has not been evaluated. Aims: To conduct sub-chronic toxic effects of CPH pectin in Sprague Dawley rats to assess its safety as a pharmaceutical grade excipient. Methods: CPH pectin at doses of 0.714, 7.14, and 71.4 mg/kg were administered to male and female Sprague-Dawley rats by oral gavage over a 90-day period. Parameters assessed were food and water intake, urinalysis, serum biochemistry, wet organ weights, histopathology and pentobarbital-induced sleeping time. Results: CPH pectin at the orally administered doses had no significant effects on feed and water intake nor on biochemical parameters, except elevations in alkaline phosphatase at the medium and high dose in the female rat. There were also reductions in creatine kinase in both male and female rats at the medium dose after 60 days, suggesting a potential cardioprotective effect of CPH pectin. Conclusions: There were no adverse effects of CPH pectin on the kidneys, wet organ weights and histopathology of the rat tissues. Subchronic administration of cocoa pod husk pectin therefore, has no significant toxic effects.